Recent Advances and Perspectives on the Use of Mineralocorticoid Receptor Antagonists for the Treatment of Hypertension and Chronic Kidney Disease: A Review - Kisho Miyasako; Yujiro Maeoka; Takao Masaki (Biomedicines)
Chronic kidney disease (CKD) is a major public health concern around the world. It is a significant risk factor for cardiovascular disease (CVD), and, as it progresses, the risk of cardiovascular events increases. Furthermore, end-stage kidney disease severely affects life expectancy and quality of life. Type 2 diabetes and hypertension are not only primary causes of CKD but also independent risk factors for CVD, which underscores the importance of effective treatment strategies for these conditions. The current therapies, including angiotensin-converting enzyme inhibitors, angiotensin II receptor blockers, and sodium–glucose co-transporter 2 inhibitors, are administered to control hypertension, slow the progression of CKD, and reduce cardiovascular risk. However, their efficacy remains suboptimal in certain instances. Mineralocorticoid receptor (MR), a nuclear receptor found in various tissues, such as the kidney and heart, plays a pivotal role in the progression of CKD. Overactivation of MR triggers inflammation and fibrosis, which exacerbates kidney damage and accelerates disease progression. MR antagonists (MRAs) have substantial beneficial effects in patients with cardiac and renal conditions; however, their use has been constrained because of adverse effects, such as hyperkalemia and kidney dysfunction. Recently, novel non-steroidal MRAs are more efficacious and have superior safety profiles to steroidal MRAs, making them promising potential components of future treatment strategies. Here, we discuss recent findings and the roles of MRAs in the management of hypertension and CKD, with a focus on the evidence obtained from fundamental research and major clinical trials.